(untitled) (REMUNOM, 2024)
The expansion of the urban area is driven by the significant population growth the city has experienced over the past two decades. This urban concentration has led to profound changes in the landscape, resulting from shifts in land use and occupancy patterns. Therefore, studying environmental perception is crucial for understanding the interplay between humans and their living environment. In this context, the overall objective of this study was to describe the environmental perception of residents in Vila do Rio Ariaú, an area located near the forest and along the water body in the metropolitan region of Manaus, Amazonas. The study involved interviewing residents of the village situated along the banks of the Ariaú River. Data collection occurred through the application of a semi-structured questionnaire and was analyzed descriptively over two days. A total of 27 individuals were interviewed, including 17 men and 10 women, with ages ranging from 19 to 71 years (mean age 43.48 ± 14.18). Most interviewees had completed secondary education. The village relies primarily on wells for water supply, with the water treated using sodium hypochlorite. The majority of respondents were aware of the risks associated with using untreated river water for consumption and actively collected litter when they observed it being discarded into the rivers. Additionally, they stay informed about environmental conservation through internet resources. Environmental education initiatives targeting these communities are essential, given their direct interaction with water resources. They can act as stewards, promoting responsible use and conservation of this environment.